Nation, Indigenization, the Beothuk:: A Newfoundland Myth of Origin in Patrick Kavanagh’s Gaff Topsails - Delisle, Jennifer (Studies in Canadian Literature, 2006)
The narrative of a national culture often begins with a "foundational myth," a story that, as Stuart Hall writes, "locates the origin of the nation, the people, and their national character so early that they are lost in the mists of, not 'real,' but 'mythic' time." For postcolonial nation, such origin myths are useful for constructing an identity that preceded, and therefore exists in defiance of, "the ruptures of colonization," and that unifies many cultures and societies into "one people." But what about invader-settler colonies? While motivated by the same desire to create a national identity that stands against the imperial motherland, these states cannot construct their origins so easily, for the "narrative of the nation" must begin with the troublesome moment of colonial invasion. In his 1996 novel Gaff Topsails, Patrick Kavanagh creates a myth for the "primordial" national identity of Newfoundland. Kavanagh's myth reconfigures the colonial moment as a myth of indigenous birth. His work is an attempt to write a national narrative of Newfoundland that serves to distance Newfoundlanders both from colonial exploiters and from Canadian identity.